Identification of the Chemical Constituents of an Anti-Arthritic Chinese Medicine Wen Luo Yin by Liquid Chromatography Coupled with Mass Spectrometry - Huanyu Guan; Xiaomei Luo; Xiaoyan Chang; Meifeng Su; Zhuangzhuang Li; Pengfei Li; Xiaoming Wang; Yue Shi (Molecules, 2019)
Wen Luo Yin (WLY), a well-known traditional Chinese medicine formulation, has been used as a complementary therapy for the treatment of rheumatoid arthritis in clinical settings. However, the chemical constituents of WLY remain unclear. In this study, a high-performance liquid chromatography coupled with tandem mass spectrometry method was established to separate and comprehensively identify the chemical constituents of WLY. The analytes were eluted with a mobile phase of acetonitrile and 0.1% aqueous acetic acid. Mass detection was performed in both positive and negative ion mode. The MS/MS fragmentation pathways were proposed for the identification of the components. A total of 42 compounds including sesquiterpenes, alkaloids, biflavonoids, polyacetylenes, phenylpropanoids and acetylenic phenols were identified unambiguously or tentatively according to their retention times and mass behavior with those of authentic standards or literature data. The identification and structural elucidation of chemical constituents may provide important information for quality control and pharmacological research of WLY.